Epentesis Vokal Baku pada Kata Serapan Bahasa Jepang dari Bahasa Arab Termin Keislaman - Dewi Isnawati; Vera Yulianti (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2022)
The epenthesis of a vowel in Japanese loanwords (onintenka), not to mention from the Arabic language, is occurred generally tends into the category of default vowel. This default vowel of epenthesis often makes the difficult for Japanese language learners to write or to understand the writing of loanwords from other foreign languages into the Japanese language. Therefore, the purpose of this research is to examine the phonological process of default vowels of epenthesis on Japanese loanwords from Arabic, particularly those related in terms of Islamic words. The resource of the data was from an Islamic website written in the Japanese language by Japanese native speakers. The results of this study show that epenthesis in the Japanese language from the Arabic language were occurred in the epenthesis of vowel “o” and “u” in the middle and at the end of the loanwords syllable.